Mammal Practicum Based on Interactive Flipbook E-Module A Solution for Enhancing Critical Thinking in Biology Education Students - Cahyati, Fitria Nur; Wahyuni, Metig Dwi; Ristanto, Rizhal Hendi; Isfaeni, Hanum (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This study aims to develop an interactive flipbook-based e-module as a learning medium for the mammal practicum to enhance the critical thinking skills of biology education students. The research employed a research and development (R&D) approach using the Hannafin and Peck model, which includes three main stages: needs analysis, design and development, and implementation with evaluation. The participants involved were biology education students enrolled in the mammal practicum course. Data were collected through expert validation questionnaires for both content and media, as well as critical thinking tests. The validation results indicated that the developed e-module met the feasibility standards in terms of both content accuracy and visual presentation. Limited trials showed a notable improvement in students’ critical thinking abilities after using the e-module. Therefore, the interactive flipbook-based e-module is considered effective and suitable as an alternative learning medium in mammal practicum sessions to support students’ critical thinking development.